(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the key environmental challenges arising during the transition to a green economy, with particular emphasis on global climate change, environmental pollution, and the inefficient use of natural resources. Since the second half of the twentieth century, intensified human economic activity has led to a sharp increase in greenhouse gas emissions, transforming climate change into a global environmental, economic, and social challenge. The study analyzes the impacts of climate change on ecological stability, economic growth, and social welfare, highlighting its consequences for the agricultural sector, energy systems, and insurance markets. In addition, the article reviews international frameworks and policy initiatives, including the United Nations Sustainable Development Goals (SDGs 2030), the Paris Agreement, and the Sendai Framework for Disaster Risk Reduction. The findings demonstrate that the implementation of renewable energy sources, green technologies, and coordinated international cooperation plays a crucial role in mitigating climate risks and ensuring sustainable development for future generations.